1984
DOI: 10.1126/science.226.4679.1189
|View full text |Cite
|
Sign up to set email alerts
|

The East Coast Magnetic Anomaly

Abstract: A model is proposed for the East Coast Magnetic Anomaly that, for the first time, incorporates an observed basement feature-a normal fault that consistently lies below the landward flank of the anomaly. The East Coast Magnetic Anomaly is similar to slope anomalies found over passive continental margins in many parts of the world. Thus the proposed model can be used to interpret slope anomalies in general.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…It can be traced laterally for 600 km before terminating against or merging with the East Coast Magnetic Anomaly (ECMA), which is a 48-km-wide, through going magnetic high along the rifted Atlantic margin of Laurentia (e.g., Vogt, 1986;Klitgord and Schouten, 1986, and references therein). The ECMA, which can be traced for more than 3000 km, has been interpreted variously: as an edge effect; as a dike suite; as a series of seaward-dipping reflectors containing tilted basalt flows; and as a deep-seated mafic intrusion (e.g., Alsop and Talwani, 1984;Keen, 1969;Keller et al, 1954;Oh et al, 1995) along or near the continent-ocean transition (Vogt, 1973;Vogt and Einwich, 1979)) Nelson et al (1985a,b) and McBride and Nelson (1988) suggested the ECMA may represent a Paleozoic suture. Thus the ECMA was probably emplaced 175-190 Ma (Vogt and Einwich, 1979;Klitgord and Grow, 1980;Sheridan, 1983;Alsop and Talwani, 1984) possibly along or near the relict suture during early rifting leading to successful opening of the Atlantic Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…It can be traced laterally for 600 km before terminating against or merging with the East Coast Magnetic Anomaly (ECMA), which is a 48-km-wide, through going magnetic high along the rifted Atlantic margin of Laurentia (e.g., Vogt, 1986;Klitgord and Schouten, 1986, and references therein). The ECMA, which can be traced for more than 3000 km, has been interpreted variously: as an edge effect; as a dike suite; as a series of seaward-dipping reflectors containing tilted basalt flows; and as a deep-seated mafic intrusion (e.g., Alsop and Talwani, 1984;Keen, 1969;Keller et al, 1954;Oh et al, 1995) along or near the continent-ocean transition (Vogt, 1973;Vogt and Einwich, 1979)) Nelson et al (1985a,b) and McBride and Nelson (1988) suggested the ECMA may represent a Paleozoic suture. Thus the ECMA was probably emplaced 175-190 Ma (Vogt and Einwich, 1979;Klitgord and Grow, 1980;Sheridan, 1983;Alsop and Talwani, 1984) possibly along or near the relict suture during early rifting leading to successful opening of the Atlantic Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…The ECMA is a distinct magnetic high running parallel to the margin from the Blake Spur fracture zone (FZ) to Nova Scotia and is often taken to mark the continent-ocean boundary. Hypothesized sources for the ECMA include a highly magnetized ridge or intrabasement dike [Klitgord and Behrendt, 1979], faulting associated with rifting [Alsop and Talwani, 1984], an edge effect between transitional and oceanic crust [Hutchinson et al, 1983], and rift-related volcanics [Austin et al, 1990]. However, recent magnetics modeling of across-margin seismic refraction profiles strongly support the last mechanism as the source of the ECMA [Austin et al, 1990;Talwani et al, 1995].…”
Section: Geologic Settingmentioning
confidence: 99%
“…A steep hinge zone and landward-dipping block faults are characteristic of the western edge of the northern basin (Klitgord and others, 1988). The postrift unconformity is at a depth of over 13 km, and the seaward end of this surface terminates at a fault known as the East Coast boundary fault that is coincident with the ECMA (Alsop and Talwani, 1984;Klitgord and others, 1988). The carbonate bankpaleoshelf edge complex migrated seaward of this boundary fault during Jurassic time and masks the deeper structure over the zone corresponding to where salt diapirs and seaward-dipping reflectors are observed off Georges Bank.…”
Section: Multichannel Seismic Reflection Datamentioning
confidence: 96%
“…It has variously been interpreted to result from dikes (Emery and others, 1970;Alsop and Talwani, 1984), to be an edge effect due to the juxtaposition of continental crust and sedimentary units (Keen, 1969;Alsop and Talwani, 1984), or to be an edge effect due to the juxtaposition of oceanic crust and sedimentary units (Taylor and others, 1968;Klitgord and Behrendt, 1979;Hutchinson and others, 1983). The ability of different models to reproduce the shape of the anomaly reflects the nonuniqueness of the magnetic data.…”
Section: Magnetic Datamentioning
confidence: 96%
See 1 more Smart Citation